084 Treating yourself: a glucocorticoid secreting tumour suppressing myasthenia gravis. Issue 6 (24th May 2018) - Swayne, Andrew; Lane, Michael; Brown, Helen; Prain, Kerri; Wong, Richard; Gillis, David; Blum, Stefan
Abstract : Introduction: We aimed to report a single patient seen at a tertiary neurology centre with a rarely described phenomenon of interaction between myasthenia gravis and a glucocorticoid secreting tumour. Case: A 70 year old, otherwise healthy male underwent a CT imaging of his chest after being trampled by a cow. Apart from several rib fractures, this revealed a slightly lobulated but well-defined right adrenal mass. Further studies revealed elevated morning cortisol levels of 847 nmol/L (reference range 140–640 nmol/L). The mass was excised and was found to be a 60 mm by 30 mm by 25 mm lesion, which was well circumscribed. It comprised of clear cells with foamy cytoplasm and a lesser component of eosinophilic cells, consistent with a functional adrenal adenoma producing glucocorticoid. Within days of the resection the patient described becoming weaker with fatigable proximal weakness of both upper and lower limbs. Acetylcholine receptor antibodies were positive and a diagnosis of myasthenia gravis was made. Upon commencement of pyridostigmine at 60 mg TDS and prednisolone 10 mg OD the symptoms improved and the patient was able to resume his previous active lifestyle. Conclusion: The phenomenon of myasthenia gravis being suppressed by a functional adrenal adenoma has only previously been reported twice. 1 2 This case report adds to the literature and can be distinguished from the other two cases by the rapidity of onset of symptoms of myasthenia over days after tumour resection. It tells a cautionary tale of medical therapy disrupting the brittle balance of nature. References: . Petramala L, Marinelli C, Giallonardo AT, Concistre A, Lucia P, Venuta F, … Letizia C. A case report of subclinical hypercortisolism due to adrenal incidentaloma complicated by myasthenia gravis after adrenalectomy. Tumori2016;102(Suppl.2). . Topham L, Chapman A, Gibbs C, Saha M. A patient with pemphigus foliaceus and myasthenia gravis treated by a cortisol-secreting adrenal adenoma. Br J Dermatol2015;172(1):280–282.